1997
DOI: 10.1021/ma970021m
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Transfer Reactions of Nitroxides in Free Radical Polymerizations

Abstract: The kinetics of radical polymerization of styrene with nitroxide stable radicals and the corresponding hydroxylamines and secondary amine were investigated at 90 °C. The amine derivative was found to be inert. The hydroxylamine causes retardation of polymerization. The rate constant of termination of the styrene propagating radicals by hydroxylamines, C x, was found to be 0.18−0.43, depending on the structure of the nitroxyl. Nitroxide caused an induction period and retarded the rate after the induction period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 30 publications
2
44
0
Order By: Relevance
“…The gradual increase of the M -w /M -n ratio with time is ascribed to side reaction(s). These results are similar to those for the tertbutyl acrylate/DBN system, in which a decomposition of the active polymer chain end occurs through the b-proton abstraction by the nitroxyl and the subsequent hydrogen transfer reaction 13,18) . The present system possibly undergoes similar side reactions.…”
Section: Aipglc Polymerization By Using Bs-dbn Adductsupporting
confidence: 79%
“…The gradual increase of the M -w /M -n ratio with time is ascribed to side reaction(s). These results are similar to those for the tertbutyl acrylate/DBN system, in which a decomposition of the active polymer chain end occurs through the b-proton abstraction by the nitroxyl and the subsequent hydrogen transfer reaction 13,18) . The present system possibly undergoes similar side reactions.…”
Section: Aipglc Polymerization By Using Bs-dbn Adductsupporting
confidence: 79%
“…[1,5] Recently, the focus of NMP research has shifted to the development of other nitroxides, such as N-(2-methyl-2-propyl)-N-(1-diethylphosphono-2,2-dimethylpropyl)-N-oxyl [DEPN, also known as SG1; Figure 2(b)], [9,[26][27][28][29] that lead to higher polymerization rates and that also enable the controlled NMP of other monomers, such as acrylates. [1] Several side reactions can interfere with the NMP activation/deactivation, such as alkoxyamine decomposition yielding terminally unsaturated polymer and hydroxylamine, [30][31][32] chain transfer to the thus formed hydroxylamine, [33] transfer reactions involving the nitroxide, [34] and nitroxide decomposition. [9,35] For styrene, the NMP is typically performed at temperatures above 373 K, and a further complication arises due to the occurrence of thermal initiation through the Mayo mechanism ( Figure 3) by which initiator radicals are continuously generated.…”
Section: Full Papermentioning
confidence: 99%
“…Transfer reactions from radicals to TEMPO-H, regenerating the nitroxide, have been studied by Gridnev [33] and Zubenko et al [32] Based on simplified kinetic models, these authors reported values of 3: [33] and 0:2 m 3 Á mol À1 Á s À1 . [32] Using kinetic modeling, the importance of transfer reactions involving hydroxylamine has been assessed and found to be insignificant in the conditions studied in this work.…”
Section: Nmp Specific Reaction Stepsmentioning
confidence: 99%
“…The primary benzylic alkoxyamine is known to be quite stable (low dissociation rate) 34 and, therefore, leads to polydisperse polymers for styrene. 17 Because TEMPO is known to be a good hydrogen abstractor, [35][36][37] it can react with chloromethyl groups to yield the corresponding hydroxylamine TEMPOH (eq 5). Similarly, with consideration of the chlorine atom [bond dissociation energy (BDE) for C 6 H 5 OCH 2 OCl ϭ 68 kcal/mol, BDE for C 6 H 5 OCH 2 OH ϭ 85 kcal/mol), 38 the chloromethyl groups could also react with TEMPO to yield the corresponding oxoaminium chloride TEMPOCl (eq 6).…”
Section: Transfer Reaction To the Benzylic Sitementioning
confidence: 99%